High-resolution flexible X-ray luminescence imaging enabled by eco-friendly CuI scintillators - Hong, Zhongzhu; Luo, Peifu; Wu, Tingting; Wu, Qinxia; Chen, Xiaoling; Yang, Zhijian; Dai, Shuheng; Jiang, Hao; Chen, Qihao; Sun, Qiang; Xie, Lili (Frontiers in Chemistry, 2022)
Solution-processed scintillators hold great promise in fabrication of low-cost X-ray detectors. However, state of the art of these scintillators is still challenging in their environmental toxicity and instability. In this study, we develop a class of tetradecagonal CuI microcrystals as highly stable, eco-friendly, and low-cost scintillators that exhibit intense radioluminescence under X-ray irradiation. The red broadband emission is attributed to the recombination of self-trapped excitons in CuI microcrystals. We demonstrate the incorporation of such CuI microscintillator into a flexible polymer to fabricate an X-ray detector for high-resolution imaging with a spatial resolution up to 20 line pairs per millimeter (lp mm−1), which enables sharp image effects by attaching the flexible imaging detectors onto curved object surfaces.